2009
DOI: 10.1007/s10620-009-0856-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concomitant Immunomodulator Use on Long-Term Outcomes in Patients Receiving Scheduled Maintenance Infliximab

Abstract: The long-term benefits of combining scheduled infliximab with concomitant immunomodulators [azathioprine or 6-mercaptopurine (6-MP)] in patients with Crohn's disease are unclear. Historical cohort followed for 5 years after initiation of infliximab for active Crohn's disease. Data were available on 123 patients who received scheduled maintenance infliximab infusions, for up to 5 years after initiation of infliximab. Clinical remission rates in the entire cohort were 73% (82/113) at 1 year, 65% (65/100) at 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…2, 3 However, this has also resulted in care for IBD becoming increasingly complex and specialized with evolution towards therapeutic paradigms that suggest better outcomes with adoption of upfront biologic therapy early on in disease course and in combination with a conventional immunomodulators. 4, 5 …”
Section: Introductionmentioning
confidence: 99%
“…2, 3 However, this has also resulted in care for IBD becoming increasingly complex and specialized with evolution towards therapeutic paradigms that suggest better outcomes with adoption of upfront biologic therapy early on in disease course and in combination with a conventional immunomodulators. 4, 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 This medication is effective for symptom remission in patients with IBD when combined with an immunomodulator such as azathioprine or 6-mercaptopurine. 5 The addition of infliximab with an immunomodulator has been shown to be more effective than immunomodulator therapy alone, although controversy exists on the concomitant use of immunomodulators with infliximab. 6 Results of a previous pediatric study of patients with Crohn disease revealed that infliximab infusions given every 8 weeks caused significant clinical improvement, and 89% of the patients in the study also were on either azathioprine or 6-mercaptopurine.…”
Section: Discussionmentioning
confidence: 99%
“…38,104,105 In a large observational study of 614 consecutive patients followed over a median 55 months, 46% of patients who were started on episodic infliximab lost response and had to switch to a scheduled maintenance regimen. 23 Scheduled maintenance therapy is therefore superior to episodic treatment for the maintenance of remission in CD.…”
Section: Maintenance Of Remission With Anti-tnf Drugsmentioning
confidence: 99%
“…The combination of maintenance infliximab and an immunomodulator produced modest improvements in outcomes beyond maintenance infliximab alone in this cohort. 105 A similar study examined the outcome in 98 patients with CD who received infliximab and at least 6 months of immunosuppressive cotreatment with azathioprine or methotrexate. 111 Disease flares, perianal complications, and switch to adalimumab were less frequently observed, and CRP was lower in periods of treatment with, compared to periods without, concomitant immunosuppression.…”
Section: Efficacymentioning
confidence: 99%